Evaluasi Mutu Gabah Pamekasan Madura Jawa Timur - Iswahyudi Iswahyudi; Sustiyana Sustiyana; Lia Kristiana (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Pamekasan Regency is one of the rice-producing areas in Madura. The problem which is the main subject of this research is how the quality of farmer grain quality in Pamekasan Regency. The study aimed to analyze the quality of Pamekasan Regency grain. This type of research is descriptive - quantitative, namely the type of research that combines quantitative and qualitative research. The analysis states that Pamekasan grain has a quantitative percentage of an empty grain of 0.9%, 3.2% green/lime grains, 18.6% yellow/damaged grains, and 0.3% red grains. It also fulfills the requirements for grain quality qualitative consisting of four characters, namely: 1) free of pests and diseases, 2) free of foul odors, acids and other odors, 3) free of chemicals and residual fertilizers, insecticides and fungicides, and 4) unhusked rice so that it has met the requirements of SNI quality grade grain quality standards II.